2005
DOI: 10.1182/blood-2004-03-0891
|View full text |Cite
|
Sign up to set email alerts
|

Patients with acute myeloid leukemia and an activating mutation in FLT3 respond to a small-molecule FLT3 tyrosine kinase inhibitor, PKC412

Abstract: Leukemic cells from 30% of patients with acute myeloid leukemia (AML) have an activating mutation in the FLT3 (fms-like tyrosine kinase) gene, which represents a target for drug therapy. We treated 20 patients, each with mutant FLT3 relapsed/ refractory AML or high-grade myelodysplastic syndrome and not believed to be candidates for chemotherapy, with an FLT3 tyrosine kinase inhibitor, PKC412 (N-benzoylstaurosporine), at a dose of 75 mg 3 times daily by mouth. The drug was generally well tolerated, although 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
469
2
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 609 publications
(483 citation statements)
references
References 19 publications
8
469
2
4
Order By: Relevance
“…Our results are in contrast to those obtained with midostaurin in AML where inhibition of autophosphorylation of mutated Flt-3 was documented in leukaemic blasts isolated from patients receiving midostaurin (Stone et al, 2005). In 70% of AML patients, there was a 50% reduction of peripheral blood blast cells, and in 25% of patients a 50% reduction in bone marrow blast cells.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are in contrast to those obtained with midostaurin in AML where inhibition of autophosphorylation of mutated Flt-3 was documented in leukaemic blasts isolated from patients receiving midostaurin (Stone et al, 2005). In 70% of AML patients, there was a 50% reduction of peripheral blood blast cells, and in 25% of patients a 50% reduction in bone marrow blast cells.…”
Section: Discussioncontrasting
confidence: 99%
“…After the start of this trial, the final report of a Phase I study (Propper et al, 2001) suggested 75 mg bid (150 mg day À1 ) as more tolerable midostaurin dosing for longterm administration. However, a recent Phase II trial of midostaurin to inhibit activated Flt3 kinase in acute myeloid leukaemia (AML) found 225 mg day À1 well-tolerated and had promising activity (Stone et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The non-linear pharmacokinetics of CGP62221 follows the same pattern as that of midostaurin, whereas the second metabolite, CGP52421, rises over time until reaching steady-state concentrations after one month of daily treatment (33)(34)(35)(36)(37). Our data show that CGP52421 is less effective in producing growth inhibition and apoptosis in neoplastic MC when compared to midostaurin.…”
Section: Discussionmentioning
confidence: 55%
“…A remarkable phenomenon is that even in patients who have resistant disease or relapse, mediator-related symptoms improve or disappear during therapy (30). treatment, followed by a significant decrease, before reaching a stable plateau after 3-4 weeks (33)(34)(35)(36)(37). The drug has two active metabolites (Supplementary Figure S1), which result from cytochrome CYP3A4-mediated oxidation of the parent-drug (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…[107][108][109][110] PKC412 showed potential in phase-I/II trials of adult AML. 111 An international pediatric relapsed AML phase-II trial with PKC412 is currently ongoing.…”
Section: Toward Targeted Therapymentioning
confidence: 99%